Correlation between Metabolic Syndrome and Intracranial versus Extracranial Arteriosclerosis among Chinese Patients with Stroke - Chunyu LIU; Xiaodan YANG; Changqing CHEN (Tehran University of Medical Sciences, 2019)
Background: We aimed to explore the correlation between metabolic syndrome and intracranial and extracranial arteriosclerosis. Overall, 318 over 60-yr-old patients with cerebral infarction or TIA who were examined by digital subtraction angiography (DSA) in our hospital were enrolled in the study. Methods: Overall, 192 patients with intracranial and extracranial arteriosclerosis were admitted to the case group (the intracranial and extracranial arteriosclerosis group). Also, 196 patients, suffering from the same condition, were selected from our outpatient clinic and enrolled in the control group. Results: The prevalence of metabolic syndrome was 31.4%. The prevalence of each metabolic syndrome component in the intracranial arteriosclerosis group was higher than those of the extracranial arteriosclerosis and the control groups. The average component values in the intracranial arteriosclerosis group was higher than those observed in other groups. The prevalence rate of metabolic syndrome had no significant difference among different degrees of stenosis for extracranial arteriosclerosis group. There was a remarkable correlation between intracranial arteriosclerosis and metabolic syndrome (P<0.001), while no correlation was detected between extracranial arteriosclerosis and metabolic syndrome (P<0.001). We concluded that metabolic syndrome may increase the prevalence risk of intracranial arteriosclerosis. There was a significant correlation between intracranial arteriosclerosis and metabolic syndrome components including hyperglycemia and hypertension. Also, there was a significant correlation between extracranial arteriosclerosis and metabolic syndrome components including hyperglycemia. Conclusion: We believe that at least three components of metabolic syndrome can obviously increase the risk of intracranial arteriosclerosis.